STRATEGI ORANG TUA DALAM MENANAMKAN PENDIDIKAN KARAKTER ANAK PADA MASA PANDEMI COVID-19 - Lusiana Siska Nurul Azizah; Nila Ispiyana; Sinta Nuryah (Academica: Journal of Multidisciplinary Studies, 2020)
Character education is an important thing for individuals that must be instilled since childhood. The practice of cultivating character education during the pandemic Covid-19 is entirely borne by parents. This study aims to determine the strategies used by parents in cultivating children’s character education during the pandemic Covid-19. This study uses a descriptive qualitative approach and phenomenological methods. Data collection tecniques through observation and structured interviews. The result of this study show that the strategy of cultivating children’s character education during the pandemic Covid-19, there are two strategies, namely: first, habituation, and second exemplary. Keywords: character education; pandemic Covid-19; parental strategy.